2021
DOI: 10.3390/app112311318
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Headform/Helmet Friction on Head Impact Biomechanics in Oblique Impacts at Different Tangential Velocities

Abstract: Oblique impacts of the helmet against the ground are the most frequent scenarios in real-world motorcycle crashes. The combination of two factors that largely affect the results of oblique impact tests are discussed in this work. This study aims to quantify the effect of the friction at the interface between the headform and the interior of a motorcycle helmet at different magnitudes of tangential velocity. The helmeted headform, with low friction and high friction surface of the headform, was dropped against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The results showed that the headform–liner CoF plays an important role in headform’s rotational acceleration. These conclusions were further confirmed by a recent study, investigating the headform’s CoF under the oblique impact with varying tangential velocities ( Juste-Lorente et al, 2021 ). Recently, Trotta et al (2018b) attached a porcine scalp on both EN960 and HIII headforms and compared their kinematics with the bare headforms.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…The results showed that the headform–liner CoF plays an important role in headform’s rotational acceleration. These conclusions were further confirmed by a recent study, investigating the headform’s CoF under the oblique impact with varying tangential velocities ( Juste-Lorente et al, 2021 ). Recently, Trotta et al (2018b) attached a porcine scalp on both EN960 and HIII headforms and compared their kinematics with the bare headforms.…”
Section: Introductionsupporting
confidence: 77%
“…The relative differences are similar or smaller than those between the 3D-printed headform and human head (I xx : 10.2%, I yy : 2.5%, and I zz : 16.1%) ( Connor et al, 2018 ). Therefore, the Cellbond headform can better represent the MoIs of an average (western) male rider than the HIII, EN960, and 3D-printed headforms in previous studies ( Connor et al, 2018 ; Juste-Lorente et al, 2021 ).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations